Porcine Myeloid Antimicrobial Peptides: A Review of the Activity and Latest Advances - Shi, Shuaibing; Shen, Tengfei; Liu, Yongqing; Chen, Liangliang; Wang, Chen; Liao, Chengshui (Frontiers in Veterinary Science, 2021)
Traditional antibiotics have made great contributions to human health and animal husbandry since the discovery of penicillin in 1928, but bacterial resistance and drug residues are growing threats to global public health due to the long-term uncontrolled application of antibiotics. There is a critical need to develop new antimicrobial drugs to replace antibiotics. Antimicrobial peptides (AMPs) are distributed in all kingdoms of life, presenting activity against pathogens as well as anticancer, anti-inflammatory, and immunomodulatory activities; consequently, they have prospects as new potential alternatives to antibiotics. Porcine myeloid antimicrobial peptides (PMAPs), the porcine cathelicidin family of AMPs, have been reported in the literature in recent years. PMAPs have become an important research topic due to their strong antibacterial activity. This review focuses on the universal trends in the biochemical parameters, structural characteristics and biological activities of PMAPs.